An Overview of Family Support for Treatment Adherence Among Patients with Diabetes Mellitus - Ika Kusuma Widiyanti; Zahid Fikri; Lilis Setyowati; Sunardi Sunardi; Khikmatul Mu'jizah (Adi Husada Nursing Journal, 2025)
Diabetes mellitus is a chronic disease characterized by elevated blood glucose levels resulting from impaired insulin production or utilization. Managing diabetes requires long-term treatment, patient satisfaction, and strong family support. Family support has been shown to play a vital role in improving patients’ well-being; however, most previous studies have used quantitative designs and have not explored patients’ lived experiences qualitatively. This study aimed to explore and describe the forms of family support that influence treatment adherence among patients with diabetes mellitus. A qualitative research design with a case study approach was employed. Data were collected through semi-structured interviews with three participants and validated using triangulation techniques to ensure credibility. Four themes emerged from the data analysis: emotional support, informational support, instrumental support, and appraisal (esteem) support. Emotional support involved encouragement and reassurance; informational support included education on self-care and healthy living; instrumental support focused on practical assistance in managing medication and diet; and appraisal support was reflected through verbal praise and recognition. The findings highlight that family support is a key factor in promoting treatment adherence among patients with diabetes mellitus. Consistent family involvement helps reduce stress, increase self-care knowledge, foster motivation, and improve quality of life while reducing the risk of complications.